2022
DOI: 10.5194/amt-15-4047-2022
|View full text |Cite
|
Sign up to set email alerts
|

A study on the performance of low-cost sensors for source apportionment at an urban background site

Abstract: Abstract. Knowledge of air pollution sources is important in policymaking and air pollution mitigation. Until recently, source apportion analyses were limited and only possible with the use of expensive regulatory-grade instruments. In the present study we applied a two-step positive matrix factorisation (PMF) receptor analysis at a background site in Birmingham, UK using data acquired by low-cost sensors (LCSs). The application of PMF allowed for the identification of the sources that affect the local air qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…This sensor was chosen for a variety of reasons, firstly, the unit cost of the OPC-N3 is relatively low (∼£250) when compared to reference grade OPC instruments. Secondly, it is currently the low-cost OPC sensor with the most independent testing and validation in the scientific literature [ 31 , 45 ]. Thirdly, access to raw sensor information (voltages) available remotely enables high-fidelity, independent data analysis and data quality assurance processes to be undertaken.…”
Section: Methodsmentioning
confidence: 99%
“…This sensor was chosen for a variety of reasons, firstly, the unit cost of the OPC-N3 is relatively low (∼£250) when compared to reference grade OPC instruments. Secondly, it is currently the low-cost OPC sensor with the most independent testing and validation in the scientific literature [ 31 , 45 ]. Thirdly, access to raw sensor information (voltages) available remotely enables high-fidelity, independent data analysis and data quality assurance processes to be undertaken.…”
Section: Methodsmentioning
confidence: 99%
“…We follow the methodology of Hagan et al (2019) and Yang et al (2022), 21,22 where further details can be found. The method is similar to Bousiotis et al (2022) 44 and Bousiotis et al (2023) 45 who use positive matrix factorization (PMF) to infer aerosol sources. Our time series input matrix includes the entire campaign at 5 min resolution of CO, O 3 , NO, and NO 2 signals, expressed in change in voltage between the working and auxiliary electrodes (ΔmV), and the particle counts per volume (cm −3 ) in 6 size bins from the Alphasense OPC-N3.…”
Section: Colocation Analysis and Correction Factor Developmentmentioning
confidence: 97%
“…Bousiotis et al (2021) used receptor-based k-means clustering with concurrent measurements from regulatory-grade instruments and LCS to identify sources of pollution at a site in Birmingham, UK. Bousiotis et al (2022) then went on to apply PMF receptor-based analysis to apportion sources using data collected from LCS. This study also used data from reference-grade instruments and aerosol chemical speciation monitors to verify their analysis.…”
Section: Lcs For Iaq Monitoring and Source Apportionmentmentioning
confidence: 99%